Comparison of fat repositioning versus onlay segmental fat grafting in lower blepharoplasty - Hedén, Per; Fischer, Sebastian (Aesthetic surgery journal, 2021)
Lower blepharoplasty is one of the most challenging procedures in aesthetic surgery. In particular, blending the lid-cheek junction and correction of the tear trough are prone to failure and unsatisfactory outcomes.The aim of this study was to combine lower eyelid blepharoplasty with a novel technique of autologous fat grafting, commonly called segmental fat grafting, and to analyze the safety and efficacy of this approach.A retrospective analysis of 339 lower blepharoplasties was performed to compare the novel technique of segmental fat grafting to traditional fat transposition during lower blepharoplasty. Outcomes were assessed objectively by several measurements as well as via online survey of 148 invited experts in plastic surgery. Statistical analysis included t test for unpaired and paired samples as well as 1-way analysis of variance for matched data.There were no differences in baseline characteristics and comorbidities between study groups. After a mean follow-up of 12.9 months (range, 5-120 months), the group that underwent segmental fat grafting had a significant reduction in tear trough width compared compared with the group receiving lower blepharoplasty with fat transposition. Based on an expert (blinded) online survey, segmental fat grafting was superior or equal in 47% and 35% of cases, respectively. Complications (4%) and revision surgeries (9%) did not differ significantly between study groups.The novel technique of transplantation of a segmental fat graft during lower blepharoplasty is a safe and effective way to overcome tear trough deformity and blend the lid-cheek junction.
Gesehen am 16.08.2021